Answer:
0
Step-by-step explanation:
![\text{If } g(x)=f^{-1}(x);$ and:$\\g(-15)=0,$ g(0)=3, g(3)=9, g(9)=20](https://tex.z-dn.net/?f=%5Ctext%7BIf%20%7D%20g%28x%29%3Df%5E%7B-1%7D%28x%29%3B%24%20and%3A%24%5C%5Cg%28-15%29%3D0%2C%24%20%20g%280%29%3D3%2C%20%20g%283%29%3D9%2C%20%20g%289%29%3D20)
We are to determine the value of ![f(f(9)).](https://tex.z-dn.net/?f=f%28f%289%29%29.)
Now:
![g(0)=f^{-1}(0)=3\\g(3)=f^{-1}(3)=9](https://tex.z-dn.net/?f=g%280%29%3Df%5E%7B-1%7D%280%29%3D3%5C%5Cg%283%29%3Df%5E%7B-1%7D%283%29%3D9)
From:
![g(3)=f^{-1}(3)=9\\f(9)=3](https://tex.z-dn.net/?f=g%283%29%3Df%5E%7B-1%7D%283%29%3D9%5C%5Cf%289%29%3D3)
From:
![g(0)=f^{-1}(0)=3\\f(3)=0](https://tex.z-dn.net/?f=g%280%29%3Df%5E%7B-1%7D%280%29%3D3%5C%5Cf%283%29%3D0)
Therefore:
![f(f(9))=f(3)=0](https://tex.z-dn.net/?f=f%28f%289%29%29%3Df%283%29%3D0)
Answer:
it's b trust me i don't know how to explain my answer but it's b
Step-by-step explanation:
explanation
This equation is also equal to 3/4x - 2/3 + 5/6 + 2x since subtracting a negative is the same as adding a positive in the long run. First, simplify the variables to get 2 3/4x - 2/3 + 5/6. -2/3 is also equal to -4/6, so -4/6 + 5/6 is 1/6. The simplified version of this expression is 2 3/4x + 1/6. Hope this helps!
Answer:
We can think that the line of the kite is the hypotenuse of a triangle rectangle, and the altitude is one of the cathetus of the triangle.
And we know that it makes an angle of 65° with the horizontal (i guess this is measured between the hypotenuse and the horizontal adjacent to the kite.
This angle is complementary to the top angle of our triangle rectangle, such that A + 65° = 90°
A = 90° - 65° = 25°
Then the altitude of the kite is the adjacent cathetus to this angle.
We can use the relation:
sin(A) = Adjacent cathetus/hypotenuse.
Sin(25°) = X/350ft
Sin(25°)*350ft = X = 147.9m
Answer:
yes
Step-by-step explanation:
22/13 =1.69≈3.2
13/4 = 3.2